Effectiveness Of Obstetric Neonatal Emergency Preparedness Training (PPGD-ON) On Midwives' Skills At Community Health Centers - Risma; Cakrawati R Cakrawati R (International Journal of Health Sciences, 2026)
Background : Obstetric and neonatal emergencies require rapid , accurate , and standardized management to prevent maternal and neonatal morbidity and mortality . Midwives , as frontline healthcare providers in primary care settings , play an important role in recognizing emergency signs , providing initial management , stabilizing patients , and facilitating timely referral . Obstetrics and Neonatal Emergency Management Training (PPGD-ON) is an important strategy to improve midwives ' competencies and practical skills in managing emergency situations. Objective : To analyze the effectiveness of PPGD-ON training on the skills of midwives at a Primary Health Center. Methods : This study employed a quasi-experimental one-group pretest – posttest design . The sample consisted of 30 midwives selected using total sampling. Midwives ' skills were assessed before and after the training using an observational checklist for obstetric and neonatal emergency management . The two-day training consisted of theoretical sessions , discussions , demonstrations , and practical simulations . Data were analyzed using the paired t- test with a significance level of 0.05. Results : The mean skills score increased from 61.87 ± 8.24 before the training to 82.63 ± 6.71 after the training . The paired t- test demonstrated statistically​ significant difference between pre-training and post-training skills scores (p < 0.001). Conclusion : PPGD-ON training was effective in improving midwives ' skills in managing obstetric and neonatal emergencies . Regular competency-based training is recommended to maintain and improve midwives ' emergency management skills in primary healthcare settings